Stereotype Gender Equality Through Representative Speech Acts "Declare" in Podcasts - Eti Setiawati; Teddy Afriansyah (Alphabet, 2024)
The issue of gender equality has become a public concern with various perspectives and stereotypes emerging. By relating to the representative speech act of "declaring", makes this study interesting. By looking at these problems, the purposes of this study are (1) to explain the meaning of representative speech acts "declare" in the three podcasts about gender equality issues and (2) to explain stereotypes that arise against gender equality issues in the three podcasts. The method used in this study is qualitative descriptive using a sociocultural communication approach. The data in this study is in the form of verbal data. The data collection method uses free listening techniques, recording techniques, and literature studies. Data analysis techniques used refer to Miles & Hubberman. The results of the study found that there were 21 meanings of representative speech acts "declare" by grouping into several aspects of gender equality stereotypes in the three podcasts, namely 1) Education/career, 2) Social and cultural, and 3) Law. The findings from the podcast analysis have substantial implications for creators and policymakers on gender equality. Gender equality through representative speech acts "declare" becomes a lesson to be able to understand various stereotypes that arise. Keywords: Gender Equality; Representative Speech Acts; Podcast